Cooperatives and their contribution to the Milennium Goals - Morales Gutiérrez, Alfonso Carlos (Razón y fe, 2018)
We are celebrating the International Year of Cooperatives. A business institution suitable for the youngest ones, women, and the less advantaged to create wealth and to emerge from the crisis. Cooperative experiences from the most diverse parts of the world are showing it to us.